2020
DOI: 10.7150/thno.44688
|View full text |Cite
|
Sign up to set email alerts
|

Loss of SIRT4 promotes the self-renewal of Breast Cancer Stem Cells

Abstract: Rationale: It has been proposed that cancer stem/progenitor cells (or tumor-initiating cells, TICs) account for breast cancer initiation and progression. Sirtuins are nicotinamide adenine dinucleotide (NAD+)-dependent class-III histone deacetylases and mediate various basic biological processes, including metabolic homeostasis. However, interplay and cross-regulation among the sirtuin family are not fully understood. As one of the least studied sirtuin family members, the mitochondrial sirtuin SIRT4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 49 publications
(59 reference statements)
1
29
0
Order By: Relevance
“…The analysis of TCGA and 3 Gene Expression Omnibus (GEO) datasets showed that decreased SIRT4 expression correlated with increased risk of disease progression and poor clinical outcome. Besides, immunoblotting and IHC staining also showed a significant decrease in SIRT4 protein levels in breast tumor tissues ( 83 ). Wang and colleagues found that down-regulation of SIRT4 expression promoted glutamine decomposition, promoted the growth of breast-cancer cells and inhibited their apoptosis.…”
Section: Role Of Sirt4 In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of TCGA and 3 Gene Expression Omnibus (GEO) datasets showed that decreased SIRT4 expression correlated with increased risk of disease progression and poor clinical outcome. Besides, immunoblotting and IHC staining also showed a significant decrease in SIRT4 protein levels in breast tumor tissues ( 83 ). Wang and colleagues found that down-regulation of SIRT4 expression promoted glutamine decomposition, promoted the growth of breast-cancer cells and inhibited their apoptosis.…”
Section: Role Of Sirt4 In Cancermentioning
confidence: 99%
“…SIRT4 deficiency increases the expression of acetyl-histone H3 at lys9 (H3K9ac), acetyl-histone H4 at lys16 (H4K16ac) and stem-cell markers, and down-regulates BRCA1 expression by regulating H4K16ac rather than well-defined H3K9ac. These processes cannot be separated from SIRT1, which regulates the acetylation pattern of histone H4 and regulates stemness through BRCA1 ( 83 ) ( Figure 6 ).…”
Section: Role Of Sirt4 In Cancermentioning
confidence: 99%
“…Recent studies have demonstrated that tumor progression and metastasis may be linked to the emergence of cancer stem cells 2 - 5 . However, our current understanding of which factor(s) drive the stemness signaling pathways in breast cancer remains limited even though much progress has occurred in the area of tumor progression 6 - 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Phospholipid scramblase 1 (PLSCR1) enhanced stem cell-like properties through upregulating signal transducer as well as activator of transcription 1 (STAT1) expression in basal-like breast cancer (BLBC) 20 . Additionally, loss of SIRT4 promoted self-renewal and expansion of BCSCs through suppressing glutamine metabolism in mitochondrial and SIRT1-mediated BRCA1 transcription in nucleus, which provided a novel cross-talk between mitochondrial and nuclear sirtuins 21 .…”
Section: Cancer Stem Cells (Cscs)mentioning
confidence: 99%